Retrospective study of Masjid Kampong Laut Palekbang, Kelantan: the significant historical values flooded and eroded in Sungai Kelantan - Ismail, Nor Atiah; Mohd Ariffin, Noor Fazamimah; Mohd Yunos, Mohd Yazid; Ismail, Sumarni; Utaberta, Nangkula (American-Eurasian Network for Scientific Information, 2015)
Background: The Sungai Kelantan riverine cultural landscape is part and parcel of its surrounding natural environment; it is a refinement of what was wild at one time. Spatial and substance organized in the landscape produce a place that makes sense of the world around them and is naturally designed to present their understanding and satisfaction about nature in their individual territory. It becomes a space for all purposes and gives a sense of pride to be part of and to share with the community. Objectives: This paper brings retrospective historical study of Masjid Kampong Laut of Palekbang, Kelantan in order to understand and appreciate the characteristic of cultural landscape in the villages that are flood prone along Kelantan River Basin. Results: Result of this investigation reveals that flood in Kelantan shares a prominent historical legacy when one of the earliest mosque in Malaysia has to be relocated in the process of preserving and conserving a traditional heritage. Conclusion: The continuous flood occurrences along the riverbank of Sungai Kelantan did not washes away history, tradition and soul of place. It is indeed, enriching the local values, culture and creating places with genuine local wisdom.